Electroconvulsive treatment of a patient with Parkinson’s disease and moderate depression - John Erik Berg (Mental Illness)
Depression is a usual comorbidity in patients with Parkinson’s disease. It has been known for more than 50 years that electroconvulsive treatment (ECT) has a positive effect on the muscular symptoms of Parkinson’s disease. Many countries do not allow giving ECT for this indication. We have recently treated a resident patient in an acute psychiatric facility referred to the hospital with moderate depressive symptoms and strong suicidal ideation. Before and after a series of ECT he filled out the Beck Depression Inventory and the Antonovsky Sense of Coherence test. The scores before ECT were 20 and 2.69, respectively, and after 12 treatments 14 and 3.38. Both test results indicate improvement regarding level of depression and coping in life. The physiotherapists treating him observed that his rigidity was reduced and his gait improved. Muscular tonus was reduced and increased his tendency of falling as he had less tonus in muscles close to joints. Self help efficiency in daily tasks improved. He got cognitive impairment during and in the weeks after ECT. Electroconvulsive treatment should be offered to more patients with Parkinson disease and depression in order to lessen the burden of both depression and Parkinson symptoms.